DEVELOPMENT OF INTEGRATED ISLAMIC SCHOOL CURRICULUM AT JUNIOR HIGH SCHOOL LEVEL IN ISLAMIC BOARDING SCHOOLS - salmon, Yoseph; Saefudin, Didin; Mujahidin, Endin; Husaini, Adian (Riviera Publishing, 2023)
This research focuses on describing and discovering a model for developing the Islamic boarding school curriculum at the junior high school level in integrated Islamic schools, where the presence of Islamic boarding schools is an integral part of the education model. Initially, as a full-day school, the concept of boarding school or Islamic boarding school emerged. In facing the expansion and development of Islamic schools, developing a curriculum model based on current products and the education market is essential. Education actors must be wise in preparing curriculum composition or structure that can adapt to recent developments. Actors in Islamic religious education and science will contribute maximally to determining curriculum content so that the Islamic Boarding School curriculum becomes at the forefront. This research aims to explore the integrated Islamic school model starting from the philosophical roots of the curriculum. By taking the example of the Ibnu Salam Nurul Fikri Boarding School in Serang, Banten, as a pioneer of integrated Islamic school-based Islamic boarding schools, it was found that the curriculum structure always refers to the national curriculum. Educational institutions' religious and scientific camps have become an unavoidable dualistic reality. This research seeks to develop the Islamic Boarding School curriculum structure at integrated Islamic schools at the junior high school level. The field study results show that the Islamic boarding school continues to prioritize science (dikes) as its curriculum philosophy, intending to produce quality graduates for state universities. This research uses qualitative methods with literature study and interviews as procedures, creating descriptive data from participants in written and oral form.